2008
DOI: 10.1007/s10552-008-9198-6
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and prostate cancer risk in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial

Abstract: In this study, diabetes showed divergent relations with prostate cancer by tumor aggressiveness. Specifically, diabetes was inversely associated with early stage prostate cancer but it showed no relation with aggressive prostate cancer. Exploratory analyses suggested a positive association between diabetes and aggressive prostate cancer in the subgroup of men with a low BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 68 publications
(96 reference statements)
7
52
0
2
Order By: Relevance
“…It appears to decrease mainly the risk of low-grade prostate cancer, and to a lesser degree that of highgrade prostate cancer. [15][16][17] However, different findings have also been reported. Recent publications showed that it may actually increase the risk of prostate cancer 18 and prostate cancer mortality 19 in Taiwanese population, who should have similar or identical genetic background to the patient population in our study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It appears to decrease mainly the risk of low-grade prostate cancer, and to a lesser degree that of highgrade prostate cancer. [15][16][17] However, different findings have also been reported. Recent publications showed that it may actually increase the risk of prostate cancer 18 and prostate cancer mortality 19 in Taiwanese population, who should have similar or identical genetic background to the patient population in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Diabetes causes many complications in multiple organs and may be related to cancer risks. 15 Most available clinical studies showed that diabetes decreases the risk of prostate cancer in general. It appears to decrease mainly the risk of low-grade prostate cancer, and to a lesser degree that of highgrade prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 13 relevant studies on the association between DM and PCa have been published since 2006, consisting of 8 prospective studies (Calton et al, 2007;Velicer et al, 2007;Leitzmann et al, 2008;Kasper et al, 2009;Wallstrom et al, 2009;Waters et al, 2009;Li et al, 2010;Lee et al, 2012) and 5 retrospective ones (Gong et al, 2006;Pierce et al, 2008;Baradaran et al, 2009;Pelucchi et al, 2011;Turner et al, 2011). With more than 30,000 additional PCa cases, we aimed to re-analyze this relationship further by conducting an updated detailed meta-analysis with focusing on the effect of time, namely the duration since DM was diagnosed and the age of patient when DM was diagnosed.…”
Section: Diabetes Mellitus Reduces Prostate Cancer Risk -No Function mentioning
confidence: 99%
“…An inverse association of diabetes with prostatic cancer has been noted in several studies, which may be due to reduced testosterone levels in diabetes, altered insulin and leptin concentrations, statins and metformin use, and changes in diet and lifestyle in controlling diabetes (Kasper and Giovannucci, 2006;Avci et al, 2013;Fall et al, 2013;Demir et al, 2014). Several studies have reported decreased PCa risk among those with DM, and others found either no protective effect or even an elevated risk (Bonovas et al, 2004;Gong et al, 2006;Leitzmann et al, 2008;Hong et al, 2011;Wu et al, 2011;Long et al, 2012 lower risk of developing prostate cancer. In addition, the mechanism through which DM and prostate cancer are related has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some authors (Leitzmann et al, 2008;Wu et al, 2011) classified the correlation between DM and PCa according to tumor grade and have reported that DM mainly decreases the risk of low-grade tumors and, to a lesser degree, the risk of high-grade tumors. Consequently, it is plausible to assume that DM changes the proportions of PCa grades favoring high-grade tumors.…”
Section: Introductionmentioning
confidence: 99%